Methemoglobin binding to model phospholipid membranes - Gorbenko, G.P. (Биополимеры и клетка, 2000)
The interaction of methemoglobin with model phospholipid membranes composed of phosphatidylcholine and its mixtures with phosphatidylserine or diphosphatidylglycerol has been studied. The binding isotherms have been analyzed in terms of two-dimensional lattice models of surface adsorption and incorporation of the protein into the lipid bilayer. The binding parameters including an association constant, binding stoichiometry, enthalpy and entropy contributions to free energy change have been estimated.